Transplantation of Fetal Stem Cells: a New Horizon for Treatment of Degenerative Diseases - Farideh RAZI; Ali TOOTEE; Bagher LARIJANI; Ensieh NASLI ESFAHANI (Tehran University of Medical Sciences, 2015)
Background: The purpose of the current study was to present an overview of different types of stem-cells and their application for treatment different degenerative disorders with specific focus on ongoing clinical trials. Methods: For the purpose of the current narrative review article, a comprehensive search was carried out on the existing literature in Google Scholar, PubMed and Scopus using the keywords: stem-cell (fetal and mesenchymal), regenerative. Relevant articles published from 1957 to 2013 are extracted and presented. Results: During the past decades, different types of stem-cells (including adult and fetal) have been used for treatment of a wide range of immunologic (Severe Combined Immunodeficiency, Di George syndrome), neurologic (Parkinson's disease, Huntington Chorea, Cerebral Palsy), musculoskeletal (ALS), and cardiovascular diseases (heart failure and cardiomyopathies) as well as chronic and acute ulcers, and diabetes. Conclusion: The results of our study demonstrated that during the past decades, stem-cell technology has been applied for treatment of a wide range of degenerative disorders with considerable success. The current ongoing clinical trials clearly demonstrate a great potential and a promising future for the technology in terms of offering curative treatment for a wide range of hitherto-incurable diseases.   Keywords: Stem cell, Transplantation, Treatment, Review Article